Pengkajian Rasionalitas Antibiotika Pada Pasien Ispa Dengan Metode Gyssens Di Puskesmas Wilayah Surakarta - Waty, Carolina Eka; Aditya P, Avianti Eka Dewi; Keswara, Yane Dila (Jurusan Farmasi, Poltekkes Kemenkes Palembang, 2023)
Background: The irrational use of antibiotics in upper respiratory tract infections is one of the causes of the high rate of resistance in the community. Antibiotics are a treatment that is still often used in prescription by doctors even though most of the causes of upper respiratory tract infections are viruses. The success of ARI therapy really depends on the accuracy of using antibiotics. The purpose of this study was to evaluate the use of antibiotics with the Gyssens method in patients with ARD in outpatient pharmacy installations in the Surakarta health center. Methods: Non-experimental research with cross sectional design with retrospective data collection techniques from patient medical records at the Surakarta Regional Health Center. Results: The results showed 76.4% of the rationality of the accuracy of the use of antibiotics in patients with ARD at the outpatient pharmacy installation at the Surakarta health center and 23.6% of the use of antibiotics was irrational which consisted of inappropriate doses and intervals, and there were alternative drugs that were more effective and cheaper. Antibiotics were also incorrectly dosed by 23%. Conclusion: The rationality for the appropriate use of antibiotics in patients who met the inclusion criteria was 516 patients. The highest use of antibiotics in ISPA patients was Amoxicillin, 442 patients, namely 85.7%, the second highest was Cefadroxil, namely 8.7%, 45 people and the third highest was Cefixime, namely 3.3%, 17 people. The accuracy of antibiotic use in outpatient ISPA patients in the Surakarta regional health center using the Gysens method was 76.4%, as many as 394 people used antibiotics rationally, and the inappropriate use of antibiotics was 23.6%, consisting of 9.3% of inappropriate antibiotic use, incorrect interval 0.2%, cheap and effective alternative drugs 10.3%, alternative drugs cheaper, effective but with inappropriate dosage 3.3%, alternative cheap, effective drugs and inappropriate intervals 0.4%, alternative cheap, effective drugs and inappropriate doses and intervals of 0.2%. Keywords : Antibiotic, ISPA, Drug accuracy, Accuracy of dosage